ChemInform Abstract: Total Synthesis of (‐)‐Hymenosetin. Issue 20 (April 2016) - Kauhl, Ulrich; Andernach, Lars; Weck, Stefan; Sandjo, Louis P.; Jacob, Stefan; Thines, Eckhard; Opatz, Till
Abstract: Hymenosetin (I) and its N‐methyl analogue are prepared in 11 and 8 steps, respectively, from citronellal employing an intramolecular Diels‐Alder reaction as the key step.